Bond strength to root dentin and fluid filtration test of AH Plus/gutta-percha, EndoREZ and RealSeal systems - Alaa Abdul Mahdi; Victoria Bolanos-Carmona; Santiago Gonzalez-Lopez (University of São Paulo, 2013)
OBJECTIVES: To investigate the bond strength and seal ability produced by AH Plus/gutta-percha, EndoREZ and RealSeal systems to root canal dentin. MATERIAL AND METHODS: Sixty extracted single-root human teeth, instrumented manually to size 40, were divided into three groups (n=20) according to the sealer used; G1: AH Plus, G2: EndoREZ, and G3: RealSeal sealers. After filling using the lateral condensation technique, each sealer group was randomly divided into two subgroups according to the tests applied (n=10 for µPush-out test and n=10 for fluid filtration test). A fluid filtration method was used for quantitative evaluation of apical leakage. Four 1-mm-thick slices (cervical and medium level) were obtained from each root sample and a µPush-out test was performed. Failure modes were examined under microscopy at 40x, and a one-way ANOVA was applied to analyze the permeability. Non-parametrical statistics for related (Friedman's and Wilcoxon's rank tests) or unrelated samples (Kruskal-Wallis' and Mann-Whitney's tests) allowed for comparisons of µPush-out strength values among materials at the different levels. Statistical significance was accepted for p values <.05. RESULTS: There are no significant differences among fluid filtration of the three sealers. The sealer/core material does not significantly influence the µPush-out bond strength values (F=2.49; p=0.10), although statistically significant differences were detected with regard to root level (Chi2=23.93; p<0.001). AH Plus and RealSeal obtained higher bond strength to intraradicular dentin in the medium root slices. CONCLUSIONS: There are no significant differences between the permeability and global µPush-out bond strength to root canal dentin achieved by AH Plus/gutta-percha, EndoREZ and RealSeal systems.